Bond strength to dentin of two endodontic sealant cements after intracanal medication of calcium hydroxide with two types of vehicles - Reinoso Trabucco, Angela Carolina (2020)
Objective: Compare the dentin bond strength of Grossman´s sealer (Grossdent) and Apexit Plus sealer (IvoclarVivadent) after intra-canal medication of calcium hydroxide Ca(OH)2 associated with vehicles of camphorated parachlorophenol (CMPC) and chlorhexidine 2% (CHX). Methodology: This was an in vitro experimental study. A sample of 44 monoradicular human teeth were disinfected and divided into 4 groups of intra-canal medication (N= 9) and 2 control groups. The teeth were disinfected and root canals were instrumented using a hybrid technique. Two groups were medicated with Ca(OH)2 and CMPC and two groups with Ca(OH)2 and CHX 2% for two weeks. One group of each medication was filled with Grossman´s sealer and the others with Apexit Plus sealer using the lateral compaction technique. The control groups were filled only with the two sealers mentioned previously. Samples were cut into 2 mm thick discs and placed on a push test with a universal testing machine. Results: The highest value of the means was obtainedby the group medicated with Ca(OH)2 in association with CMPC and filled with Apexit Plus (m 3.742; SD 0.808), while the lowest value was presented by the group of Ca(OH)2 associated with CMPC, filled with Grossman´s sealer (m 1,371; SD 0.699). Statistical differences were considered with p<0.001. Conclusion: Root dentin bond strength is influenced by intra-canal medication prior to endodontic filling.